Mekanik sistemlerin hareket analizlerinin ve simülasyonunun bilgisayar ortamında gerçekleştirilmesi - Ekici, Hikmet Nazım (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2008)
Makine ve takım tezgahlarında birbiriyle baglantılı hareket eden uzuvlar mekanizmalarıolustururlar. Makineler tasarlanırken çok sayıda uzvun birbirine olan etkileri ve uzuvhareketlerinin hesaplanması gerekir. Bu amaçla onları bilgisayar ortamında tasarlayıphareketlerini analiz etmek çok daha kolay ve zaman kazandıran bir yöntemdir. Ancak ülkemizdebu çok az kullanılan bir mühendislik uygulamasıdır. İlgisizligin yanında ülke sanayinin bu türteorik çalısmaları destekleyecek asamaya ulasmaması bu konunun ve bu tezin uygulama alanınıkısıtlamaktadır. Bu çalısmada Adams Programı kullanılarak 5 ayrı tasarım yapılmıstır. İlk olarakbir yay-sönümleyici tasarımı yapılmıs, simüle edilmis ve analitik çözümü bulunmustur. 4 çubukmekanizması, krank- biyel mekanizması, vargel tezgahının çalısma mekanizmaları tasarlanıpsimüle edilmis ve analitik çözümleri bulunmustur. Vargel tezgahı tasarımı için Anova analiziyapılarak optimum bir tezgah tasarımı elde edilmeye çalısılmıstır. Ardından 4 silindirli içtenyanmalı bir motor tasarlanmıs ve motorun simülasyonu yapıldıktan sonra pistonlara etkiyen itmekuvveti, volan dislisi torku bulunmustur. Son olarak bu çalısmada genisçe bir ekler bölümüyazılmıstır. Ekler bölümünde Adams Programının kullanımı anlatılmıs, 2 uygulama yapılmıs,çalısma boyunca yapılan tasarımların teknik detayları anlatılmıs ve tasarımların kaynak kodlarıverilmistir. Ekler bölümünün içerigi konuya yabancı olanlara yardımcı olacak niteliktedir.

Mechanisms are parts which move in harmony while connected to each other in certaincalculations. When designing mechanisms, the relation of these parts to each other and thecalculations done regarding the possible motions of these parts are essential. For this reason theneed of using computer sciences in order to design and analyze such parts for less timeconsuming and more accurate matters is widely accepted method. Unfortunately in our owncountry this method is rather a less preferred one. Maybe ignorance is the reason but whatever thereason is our own industry is not in the position to support efforts to be spent on this method andthat narrows the application areas of the matter to be stated in this thesis. In this piece of work,the program Adams is used to produce five different designs. First design is about a springdamper.It has been simulated and its analytical solution is stated. Then 4 bar mechanism, crankrodmechanism, shaper mechanism designs have been produced, simulated and their analyticalsolutions are stated. For the shaper mechanism design Anova analyze has been completed and bythis mean an optimum machine design is intended to be produced. Then a internal combustionengine with 4 cylinders is designed and after its simulation is completed, the force pushing thepistons and torsional damper torque is calculated. At the end of this thesis, there is a wideappendix section is put. In the appendix section, Adams Program is described and information ofhow to use the program is given as well as two examples given to support the explanations. Alsoin this appendix section the technical details of the designs that are made for this piece of work isgiven and the source codes of these designs are supplied. The total content of the appendixsection is prepared with the intention of providing help for understanding for those who are notfamiliar with the issues that are covered in this thesis.
Analysis and simulation of mechanical system motions in computer environment
Keywords: Makine Mühendisliği; Mechanical Engineering; Teknik Eğitim